The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/10447318.2020.1848161
|View full text |Cite
|
Sign up to set email alerts
|

A Reflection on Virtual Reality Design for Psychological, Cognitive and Behavioral Interventions: Design Needs, Opportunities and Challenges

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Previous studies have shown how co-design techniques can be effectively used to design virtual scenarios related to specific situations, as it allows to obtain valuable information from experts in the reference sector (Eisapour et al, 2020 ). In our case, we have chosen to also involve HCI experts and VE designers from the beginning, a choice that was made only in a few of the previous works (Bettelli et al, 2019 ; Tabbaa et al, 2020 ). Involving this type of experts from the early design stages allowed us to focus not only on the contents of the VR environment (e.g., danger indicators of a flood, correct evacuation behaviors), but also on the technical aspects and interactive modalities (e.g., feedback, gamification elements), obtaining a global view of the various parts to be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown how co-design techniques can be effectively used to design virtual scenarios related to specific situations, as it allows to obtain valuable information from experts in the reference sector (Eisapour et al, 2020 ). In our case, we have chosen to also involve HCI experts and VE designers from the beginning, a choice that was made only in a few of the previous works (Bettelli et al, 2019 ; Tabbaa et al, 2020 ). Involving this type of experts from the early design stages allowed us to focus not only on the contents of the VR environment (e.g., danger indicators of a flood, correct evacuation behaviors), but also on the technical aspects and interactive modalities (e.g., feedback, gamification elements), obtaining a global view of the various parts to be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, co-design has been effectively applied in other areas related to VR experience. It was mainly used in mental health domain, to create virtual scenarios to facilitate psychological, cognitive, and behavioral interventions for dementia, anxiety disorder, eating disorders, pain management (Tabbaa et al, 2020), and fear of public speaking (Flobak et al, 2019). Co-design techniques have also been effectively applied to develop VR simulations and serious games to promote physical activity (Boger et al, 2018;Eisapour et al, 2020) and to enrich user experience in cultural and naturalistic site (Bettelli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Telehealth allows patients to access health care with no need to travel, and XR can further enable access to care with no need for concern they will be judged. It will be important to explore avatars in XR telehealth as a solution for stigmas of visible medical conditions (eg, skin disease and burns) [ 177 , 178 ], criminal history or potential (eg, prevention of offense related to sexual preference) [ 179 , 180 ], and provide unprecedented opportunities for mental health and wellness [ 86 , 181 , 182 ].…”
Section: Xr Telehealth After Covid-19mentioning
confidence: 99%